Double outlet right ventricle - Bell-Cheddar, Yolandee; Devine, William A.; Diaz-Castrillon, Carlos-Eduardo; Seese, Laura; Castro-Medina, Mario; Morales, Raymond; Follansbee, Christopher W.; Alsaied, Tarek; Lin, Jiuann-Huey I. (Frontiers in Pediatrics, 2023)
This review article addresses the history, morphology, anatomy, medical management, and different surgical options for patients with double outlet right ventricle.